The Rejection of Palestinian Refugees Following the October 7, 2023 Attack: A Perspective on Security and Humanity - Sitorus, Michael Daud Marsinondang; Wati, Diani Sadia (Journal of Law, Politic and Humanities, 2025)
The escalation of the Israeli-Palestinian conflict on October 7, 2023, led to a large-scale attack by Hamas, triggering a refugee crisis in Gaza and subsequent rejections by neighboring countries, including Jordan. This rejection, although in conflict with the principle of non-refoulement as a norm of international law, is viewed as a measure to protect state sovereignty. This research employs a normative juridical method, emphasizing legislative, case-based, historical, and conceptual approaches to analyze the interaction between state sovereignty and refugee protection. The main discussion includes the threats to sovereignty posed by refugees, the perspective of the non-refoulement principle as a jus cogens norm, and the implications of the resulting normative conflict. The conclusion indicates that while state sovereignty is crucial, humanitarian considerations and the rights of refugees must also be taken into account to achieve a fair and harmonious solution.